FORMS OF COMPARATIVE DEGREE OF ADJECTIVES IN UZBEK AND RUSSIAN - Dustmamatova Nilufar Pirimkulovna (Galaxy International Interdisciplinary Research Journal, 2021)
Тhe article discusses the ways of founding forms of comparative adjectives (using the example of Russian and Uzbek languages). The main attention is paid to the identification of common and specific elements of forms of comparative degree in languages belonging to different language families: Uzbek and Russian.